Nanocomposites - Recent Evolutions 2019
DOI: 10.5772/intechopen.79479
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Strontium Doped Rare Earth Manganites Nanocomposites and Their Photocatalytic Performances

Abstract: Studying catalysts in situ is an important topic that helps us to understand their surface structure and electronic states in operation. Three types of materials are used in the degradation of organic matter, which has applications in the environmental remediation and self-cleaning surfaces. The technique is widely known but still hampered by one significant limitation. The materials generally absorb ultra violet UV light but we need to develop active materials for visible light. Utilizing the sunlight efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The rare earth manganites is formed in the well-known perovskites crystal structure where they does not crystalize only in the cubic crystal system but also in the form of the orthorhombic, rhombohedral, hexagonal or monoclinic depends on the synthesis procedure and heat process. The different crystal structure systems of rare earth manganites were reported in different work, where they could be formed as cubic, orthorhombic, rhombohedral, hexagonal or monoclinic 1,3,916 . In this work, the effect 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rare earth manganites is formed in the well-known perovskites crystal structure where they does not crystalize only in the cubic crystal system but also in the form of the orthorhombic, rhombohedral, hexagonal or monoclinic depends on the synthesis procedure and heat process. The different crystal structure systems of rare earth manganites were reported in different work, where they could be formed as cubic, orthorhombic, rhombohedral, hexagonal or monoclinic 1,3,916 . In this work, the effect 48 .…”
Section: Resultsmentioning
confidence: 99%
“…The optimized band gap energy in such oxides, the doped divalent element rare-earth transition metal oxides of the perovskite-like structure, explains and enhances photogeneration of both electrons and holes and hence the separation of charge carriers 43 . More efforts and intensive research have been done and still now we need more activities in order to tuning their optical and electrical properties of these materials that may help us to control of their rational design structure by the cationic replacements in ABO 3 pervoskite 3 . The promising photocatalytic performance of the perovskite compounds are observed as a result adapting their bandgap values to the produced visible-light absorption as well as the potentials of band edge to tailor the requirements of particular photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The group of Fujimura et al were the first to report the deposition of h -YMnO 3 thin films on MgO(111), ZnO(0001), Al 2 O 3 (0001) sapphire, and Pt(111)\MgO (111) using RF magnetron sputtering (RFMS) [ 20 , 21 , 22 , 23 ]. Subsequently, other studies were made on h -YMnO 3 grown on Pt\Al 2 O 3 (0001) and on Pt\Y 2 O 3 \Si(111) structures using molecular beam epitaxy (MBE) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially the case in the present time, when the development of new and efficient solar energy conversion technologies is crucial from an environmental, social, and economic point of view. The group of Fujimura et al were the first to report the deposition of h-YMnO 3 thin films on MgO(111), ZnO(0001), Al 2 O 3 (0001) sapphire, and Pt(111)\MgO (111) using RF magnetron sputtering (RFMS) [20][21][22][23]. Subsequently, other studies were made on h-YMnO 3 grown on Pt\Al 2 O 3 (0001) and on Pt\Y 2 O 3 \Si(111) structures using molecular beam epitaxy (MBE) [24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in regard of crystallographic texture, SrTiO 3 's cubic perovskite structure is more stable than TiO 2 . (A. Abdel-Latif 2019). It has been reported that pure SrTiO 3 (Huang et al 2014;Xie et al 2018;Gao et al 2018) or ions doped SrTiO 3 (Konta et al 2004;Wu and He 2018a;Li et al 2020) can show effective photocatalysis of organic pollutants under UV or Visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%